HUBUNGAN PEMBELAJARAN ONLINE DIMASA PANDEMI COVID-19 DENGAN TINGKAT STRESS MAHASISWA UNIVERSITAS HALU OLEO TAHUN 2020 - Nunu Sarah; Hariati Lestari; Rizki Eka Sakti Octaviani Kohali (Endemis Journal, 2021)
Online learning is a learning method that is carried out using technology such as a smart phone device, computer or laptop connected to an internet network. Face-to-face learning is temporarily suspended to follow the Health protocol provided by the Government. Changes that occur in students due to Covid-19 have an impact on student psychology such as stress. The general purpose of this study was to see the relationship between online learning during the pandemic and the stress level of students at Halu Oleo University in 2020. This study was an analytic observational study with a cross sectional approach. The sample in this study used a proportional stratified random sampling technique of 366 people. Statistical test using Chi square test, collected by questionnaire method using google form. The results showed the level of stress in students of the University of Halu Oleo Kendari in 2020 who experienced low stress was 357 respondents (97.5%) and severe stress was 9 respondents (2.5%). From bold learning media (p value = 0.468), bold learning implementation (p value = 0.005), courageous learning time (p value = 0.037) and courageous learning locations (p value = 0.049). shows that there is no significant relationship between bold learning and stress levels in students.